2021
DOI: 10.1590/0037-8682-0461-2021
|View full text |Cite
|
Sign up to set email alerts
|

The seven constitutive respiratory defense barriers against SARS-CoV-2 infection

Abstract: Before eliciting an adaptive immune response, SARS-CoV-2 must overcome seven constitutive respiratory defense barriers. The first is the mucus covering the respiratory tract’s luminal surface, which entraps inhaled particles, including infectious agents, and eliminates them by mucociliary clearance. The second barrier comprises various components present in the airway lining fluid, the surfactants. Besides providing low surface tension that allows efficient gas exchange at the alveoli, surfactants inhibit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 122 publications
0
6
0
1
Order By: Relevance
“…Human MUC19 transcripts in salivary glands (n = 7) and MUC19 glycoproteins in glandular mucous cells and saliva are also found (69). Mucosal immunity including the mucus covering the respiratory tract, surfactants, anti-infectious molecules (sIgA, defensins, and interferons), respiratory epithelial cells, and innate immunity cells (nasal goblet cells and macrophages), form a mucosal barrier that plays a vital role in COVID-19 (70). The mucosal immune system in the nasal and oral cavities, acts as the first barrier, with the appearance of sIgA in the saliva (4).…”
Section: Endocrine and Immune Functions Of Salivary Glandsmentioning
confidence: 99%
“…Human MUC19 transcripts in salivary glands (n = 7) and MUC19 glycoproteins in glandular mucous cells and saliva are also found (69). Mucosal immunity including the mucus covering the respiratory tract, surfactants, anti-infectious molecules (sIgA, defensins, and interferons), respiratory epithelial cells, and innate immunity cells (nasal goblet cells and macrophages), form a mucosal barrier that plays a vital role in COVID-19 (70). The mucosal immune system in the nasal and oral cavities, acts as the first barrier, with the appearance of sIgA in the saliva (4).…”
Section: Endocrine and Immune Functions Of Salivary Glandsmentioning
confidence: 99%
“…Помимо обеспечения низкого поверхностного натяжения, обеспечиваю щего эффективный газообмен в альвеолах, сурфактантная система легких обладает способностью предотвращать непосредственное воздействие вируса на клетку за счет возможности сорбировать на своей поверхности вирусы и бактерии с последующим предоставлением их альвеолярным макрофагам [21,22]. Кроме того, при дефиците легочного сурфактанта из-за уменьшения продольного градиента поверхностного давления нарушается перемещение мокроты в зону мукоцилиарного транспорта, что препятcтвует санации альвеол и нижних дыхательных путей [12,14].…”
Section: Covid-19unclassified
“…In addition, IgA can neutralize extra-and intracellular pathobiont toxins as it can bind a wide range of antigens due to their low affinity. IgA antibodies can bind to lipopolysaccharides (LPS), DNAs, flagellin, capsular polysaccharides and viral components [3,39]; and can eliminate pathogens or antigens via an IgA-mediated excretory pathway that binding to IgA progresses poly-immunoglobulin receptor mediated transport of immune complexes [40]. Epithelial cells infected viruses secrete a broad range of interferons and as such can have direct immune effects and confer resistance to uninfected cells [41].…”
Section: The Lung Microbiota In Health and Disease And Lung Mucosal I...mentioning
confidence: 99%
“…The shedding of virus particles in the cell debris are then inhaled into the lung. In the lung, the virus can enter the systemic circulation with ease due to high mucosal permeability [3,4]. It has also been demonstrated that the oral cavity is also an important site for the replication of the SARS-CoV-2 virus [5].…”
Section: Introductionmentioning
confidence: 99%